2014
DOI: 10.1002/pam.21743
|View full text |Cite
|
Sign up to set email alerts
|

The Forgotten Summer: Does the Offer of College Counseling After High School Mitigate Summer Melt Among College-Intending, Low-Income High School Graduates?

Abstract: Despite decades of policy intervention to increase college entry and success among low‐income students, considerable gaps by socioeconomic status remain. To date, policymakers have overlooked the summer after high school as an important time period in students’ transition to college, yet recent research documents high rates of summer attrition from the college pipeline among college‐intending high school graduates, a phenomenon we refer to as “summer melt.” We report on two randomized trials investigating effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
119
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 25 publications
3
119
0
1
Order By: Relevance
“…To the degree that these interventions can connect students to important wraparound services with the institution, they have the potential to address nonacademic barriers to success. In experimental studies, these text-messaging interventions have demonstrated positive impacts on enrollment and persistence (Castleman and Page, 2016;Castleman, Page, and Schooley, 2014). However, the evaluated interventions largely focused on preenrollment outreach and were primarily focused on admissions and enrollment requirements rather than connecting students to wraparound supports.…”
Section: Prior Research On Wraparound Support Programs and Financial mentioning
confidence: 99%
See 2 more Smart Citations
“…To the degree that these interventions can connect students to important wraparound services with the institution, they have the potential to address nonacademic barriers to success. In experimental studies, these text-messaging interventions have demonstrated positive impacts on enrollment and persistence (Castleman and Page, 2016;Castleman, Page, and Schooley, 2014). However, the evaluated interventions largely focused on preenrollment outreach and were primarily focused on admissions and enrollment requirements rather than connecting students to wraparound supports.…”
Section: Prior Research On Wraparound Support Programs and Financial mentioning
confidence: 99%
“…Programs such as Single Stop U.S.A.'s Community College Initiative aim to offer students a better way to access public benefit programs and the broad network of wraparound services that institutions and community organizations provide. The literature indicates that programs providing wraparound services are successful in improving college outcomes for students (Avery, 2013;Castleman and Goodman, forthcoming;Scrivener, Bloom, et al, 2008;Scrivener, Weiss, et al, 2015), as are interventions that aim to connect students to financial support (Bartik, Hershbein, and Lachowska, 2015;Bettinger, 2004;Dynarski, 2008;Richburg-Hayes et al, 2009;Scott-Clayton, 2011) and interventions that provide information about or assist with complex application processes (Bet-tinger et al, 2012;Castleman and Page, 2016;Castleman, Page, and Schooley, 2014). However, there is limited research on programs such as Single Stop, which focuses exclusively on nonacademic wraparound support and facilitates access to public benefits and other resources for low-income students.…”
Section: Summary Of Findings and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students who attend selective institutions, which tend to have more resources available for student support, have better education outcomes, even after controlling for student ability" (White House 2014).We have clear evidence that students, particularly low-income ones, do not attend the highest quality colleges available to them (Bowen, Chingos, and McPherson 2009;Dillon and Smith 2013;Hoxby and Avery 2013;Smith, Pender, and Howell 2013) and that initial college choices can be altered by relatively low-cost interventions (Bettinger et al 2012;Carrell and Sacerdote 2013;Hoxby and Turner 2013;Castleman, Page, and Schooley 2014;Pallais 2015;Smith, Hurwitz, and Howell 2015). Less clear is the extent to which changing such college choices affects students' longer-run outcomes, such as degree completion and labor market earnings.…”
mentioning
confidence: 96%
“…At present, much of this work explores the ability of such interventions to influence students' choices about college-going -whether by improving student-institution matches, (Hoxby & Turner, 2014), encouraging students to apply for needbased financial aid (Bettinger et al, 2012), providing better information about the costs and payoffs of college (Oreopoulos & Dunn, 2012), or counseling students through the college transition process (Castleman, Page, & Schooley, 2014;Castleman & Page, 2015).…”
Section: B Non-pecuniary Interventions To Improve Postsecondary Persmentioning
confidence: 99%